Revealing the spatiotemporal evolution of the 2024 extreme flood in Guangdong Province: Insights from GRACE-FO and in situ measurements - Sulan Liu; Yunlong Wu; Guodong Xu; Cuiyu Xiao; Xiaohui Wu; Yulong Zhong (Journal of Hydrology: Regional Studies)
Study region: Guangdong Province, located in southern China. Study focus: This study finely quantified the spatiotemporal evolution of the flood event in April 2024. We analyzed the extreme precipitation process in the Guangdong Province based on the near real-time precipitation data from the China Meteorological Administration Land Data Assimilation System, and reconstructed the daily terrestrial water storage anomalies (TWSA) based on the Gravity Recovery and Climate Experiment Follow-On data as well as various temperature and precipitation data to monitor the spatiotemporal dynamics of the flood. Furthermore, a computationally normalized daily flood potential index (NDFPI) based on the reconstructed daily TWSA was used for flood warning. New hydrological insights for the region: The results showed that the reconstructed daily TWSA increased by 124.1 mm from April 16 to May 4, and the corresponding water storage increased by 29.3 km3 in Guangdong Province. The NDFPI issued flood warnings 2 days earlier than water level alerts at most river gauging stations, demonstrating its potential for early flood warning. Further studies showed that the El Niño Southern Oscillation is strongly correlated with TWSA and precipitation anomalies, revealing the crucial driving role of the climate patterns influenced by ENSO in extreme precipitation events. This study provides new insights into flood event monitoring and early warning in southern China.